Bahasa Idonesia - Yanti, Adri; Mayar, Farida (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to describe entrepreneurship learning for early childhood. This type of research is quantitative using the Research and Development model. The development model used is the 4-D model. Data collection techniques validation questionnaires, practicality instruments and effectiveness instruments. Data analysis techniques consist of learning validation data analysis, practical analysis of entrepreneurship learning and analysis of learning effectiveness. The results of the study illustrate that the results of observing the implementation of RPPH with a percentage of 94.25% are in the valid category, student responses to the practicality of entrepreneurship learning with a percentage of 90.25% are in the very appropriate category, teacher responses to the practicality of the Entrepreneurship Learning Module with a percentage of 90.25%, Effectiveness test, student activity with an average of 76.38 is in the high category and student learning outcomes are developing very well.